IMPACT OF OBSESSIVE COMPULSIVE DISORDER ON LECTURES ACTIVITIES - Mudarsa, Hartini (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2021)
Obsessive compulsive disorder is an anxiety disorder, in which a person's mind is filled with persistent and uncontrolled ideas, a person is forced to perform repetitive actions, causing stress and interfering with his function in daily life. This study aims to determine the impact of obsessive compulsive disorder on lecture activities. This study uses a descriptive qualitative design. Sampling in this study by means of purposive sampling. Collecting data using interview and observation techniques. The results showed that the two subjects met the clinical symptoms of obsessive compulsive disorder based on reviews from experts in DSM-IV-TR, namely: cognitive aspects such as emphasizing perfection and truth in typing their assignments, prioritizing order in their lives, thoroughness when filling lecture absences and when completing assignments. Collecting lecture assignments. Affective aspects such as always taking over all group assignments because both subjects felt that their group mates were not able to make assignments according to their wishes, and Conative aspects such as, stiff in interpersonal relationships, the main priority was assignments, had a fixed mind about the door, water taps, motorbike keys, and about hygiene. The results of this study also indicate the impact experienced by the two subjects. Such as disrupting lectures and daily activities, experiencing significant stress, always feeling tense and anxious, not being liked by college friends and spending a lot of time.